2004
DOI: 10.1002/sce.20043
|View full text |Cite
|
Sign up to set email alerts
|

Science teachers' transformations of the use of computer modeling in the classroom: Using research to inform training

Abstract: This paper, from the UK group in the STTIS (Science Teacher Training in an Information Society) project, describes research into the nature of teachers' transformations of computer modeling, and the development of related teacher training materials. Eight teacher case studies help to identify factors that favor or hinder the take-up of innovative computer tools in science classes, and to show how teachers incorporate these tools in the curriculum. The training materials use the results to provide activities en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Future research should also investigate the quality of preservice teachers' critiques and adaptations. Do the changes they suggest undermine the designers' rationale, or are they aligned with the intent of the designers (Pintó, 2005;Stylianidou, Boohan, & Ogborn, 2005)? Do the skills continue to develop over time?…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Future research should also investigate the quality of preservice teachers' critiques and adaptations. Do the changes they suggest undermine the designers' rationale, or are they aligned with the intent of the designers (Pintó, 2005;Stylianidou, Boohan, & Ogborn, 2005)? Do the skills continue to develop over time?…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Oftentimes we heard from teachers that when taking up an innovative curriculum package, they were concerned about the tensions between teaching in an innovative way and spending extra time covering the same content (Stylianidou et al 2005). Awareness was brought to the STs that school N has made the innovation a routine practice in school but at the same time did not compromise the students' academic achievement, and even so gained significant improvement.…”
Section: Resultsmentioning
confidence: 99%
“…changes of matter) (Kikas, 2004); conceptions of models and the modeling process (Crawford & Cullin, 2004); how teachers' beliefs and attitudes inform intentions (Zacharia, 2003); factors that hinder or support teacher use of modeling programs (Stylianidou, Boohan, & Ogborn, 2004) and model-based approaches (Schwarz, 2009) in science classrooms; and the role of teachers' pedagogical content knowledge (PCK) (De Jong, Van Driel, & Verloop, 2005). Based on iterative cycles designed to improve teacher knowledge of modeling-centered practices, Zacharia (2003) offered that teachers' beliefs and attitudes influence intentions to engage with computerbased models and in post interviews, revealed that teachers saw the most benefit from a combination of interactive computer-based simulations and laboratory inquiry-based experiments.…”
Section: Teacher's Views and Perceptions Of Visualization Technologiementioning
confidence: 99%